1993
DOI: 10.1080/01904169309364671
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic and toxic ion effects on seedling emergence and nutrition of citrus rootstocks

Abstract: The effects of isosmotic solutions of sodium chloride (NaCl), polyethylene glycol (PEG), and mannitol with or without supplemental calcium (Ca) were compared to separate osmotic effects from toxic ion effects of salts on seed imbibition, seedling emergence, and the early stage of seedling growth of three citrus rootstocks. The rate of seed imbibition was relatively low for sour orange (SO) in PEG treatments which caused a delay in seedling emergence. These results of PEG supported earlier findings which sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…There was no effect of controlled-release fertilizer concentrations on plant emergence ( figure 1). Citrus rootstock germination has been affected by high osmotic or salinity levels in the substrate [12,13]. In the present case, the salinity index of the fertilizer is probably not high enough to decrease germination at the concentrations tested.…”
Section: Resultsmentioning
confidence: 89%
“…There was no effect of controlled-release fertilizer concentrations on plant emergence ( figure 1). Citrus rootstock germination has been affected by high osmotic or salinity levels in the substrate [12,13]. In the present case, the salinity index of the fertilizer is probably not high enough to decrease germination at the concentrations tested.…”
Section: Resultsmentioning
confidence: 89%
“…Later, as the cotyledons slow in water uptake and expansion, Phase II begins, and the embryo axis, mainly the root, is likely the major sink for water and the toxin. Similar to citrus (Zekri, 1993), the effects of the autotoxin are mainly osmotic during the imbibition period but mainly toxic after Phase II begins. The toxin likely reduces RER while within the seed to further delay Gt 50 (Chon et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of PEG-induced water stress on growth, root density, seedling emergence, and plant water relations including leaf water potential, stomatal conductance and root hydraulic conductivity of citrus rootstocks have been investigated (Zekri, 1987;Zekri and Parsons, 1989,1990a, 1990bZekri, 1991bZekri, , 1993. However, none of these studies has shown the relationship between nutrient accumulation and concentration in the roots and nutrient translocation to the leaves.…”
Section: Introductionmentioning
confidence: 98%